The impact of adopting the two international valuation standards (400&410) IVS in accounting on real estate rental operations and its impact on the outcome of the activity (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The research aims to study the impact of adopting the international valuation standards (IVS 400&410) in evaluating real estate rental operations and the reflection of that evaluation on revenues. In order to achieve the research objective, the Diwaniyah Municipality Directorate was chosen to implement the research, and the data obtained by the researcher from the Diwaniyah Municipality Directorate related to rental operations for the years (2019-2022) were relied upon. The owners of real estate offices in the center of Diwaniyah Governorate were consulted to measure the impact of adopting the international valuation standards (IVS400&410) in accounting for rental operations and their reflection on revenues. The researcher conducted an applied study of rental operations evaluations before and after adoption and tested the hypotheses to determine their acceptability. The researcher reached a set of conclusions and recommendations. Among the most prominent conclusions reached is that adopting the revaluation process according to the international valuation standards (IVS 400&410) and relying on the market approach consistent with local laws related to real estate rental operations and consistent with the environment in which the Diwaniyah Municipality Directorate operates led to increase the rental income percentage significantly, which was reflected in the increase in the total revenues of the directorate, and thus changed the result of the directorate's activity for the years of the research sample from (deficit) to (surplus) and enabled the Diwaniyah Municipality Directorate to cover all its needs of (uses) from its achieved revenues and not need to take amounts from the state treasury to cover those needs. One of the most important recommendations reached by the research is the necessity of applying the International Evaluation Standards (IVS) based on market value and market rent (market method), which is one of the three methods included in the international evaluation standards because it leads to maximizing the revenues of the Diwaniyah Municipality Directorate in a way that the directorate's revenues are higher than its expenses, which is what self-financing government units seek.